Knowledge of learning disability among pre- and in- service teachers in Malaysia - Saad, Supiah (s.n, 2013)
Are mainstream teachers in Malaysia knowledgeable about types of students with special needs, are there enough support services as well as facilities provided for these students education? This study investigated the knowledge level of Malaysia student teachers classified as in-service student teachers (undergoing a distance learning program for Bachelor degree sponsored by the MOE(Malaysia) and pre-service student teachers (regular students undergoing bachelor in education degree)